Prevalence and predictors of anemia among children under 5 years of age in Arusha District, Tanzania - Kejo D; Petrucka PM; Martin H; Kimanya ME; Mosha TCE (Dove Medical Press, 2018)
Dyness Kejo,1 Pammla M Petrucka,1,2 Haikel Martin,1 Martin E Kimanya,1 Theobald CE Mosha3 1Department of Food Biotechnology and Nutritional Sciences, Nelson Mandela African Institution of Science and Technology (NM-AIST), Arusha, Tanzania; 2College of Nursing, University of Saskatchewan, Saskatoon, SK, Canada; 3Department of Food Technology, Nutrition and Consumer Sciences, Sokoine University of Agriculture, Morogoro, Tanzania Abstract: Anemia is a global health problem affecting most developing countries. We examined the prevalence of anemia and its predictors among children under 5 years of age in Arusha District, Tanzania. Random sampling technique was used to identify 436 children aged 6–59 months. Anemia status was assessed by measuring hemoglobin concentration from blood sample obtained from a finger prick and HemoCue® Hb 201+ photometer. Demographic information and dietary intake data were collected using a standardized questionnaire. Anemia cut-off points were defined according to World Health Organization standards for children aged 6–59 months. Logistic regression using backward procedure was used to estimate odds ratios (ORs) at 95% confidence intervals (CIs). Prevalence rate of anemia among under-fives was found to be 84.6% (n=369). Multivariable logistic regression identified the following predictors of anemia; low birth weight (adjusted OR (AOR): 2.1, 95% CI: 1.1–3.8), not consuming meat (AOR: 6.4, 95% CI: 3.2–12.9), not consuming vegetables (AOR: 2.1, 95% CI: 1.1–4.1), drinking milk (AOR: 2.5, 95% CI: 1.1–5.2), and drinking tea (AOR: 4.5, 95% CI: 1.5–13.7). It was concluded that low birth weight and dietary factors (ie, low or nonconsumption of iron-rich foods like meat, vegetables, and fruits) were predictors of anemia among under-five children living in this rural setting. Community education on exclusive breastfeeding and introduction of complementary foods should be improved. Mothers and caretakers should be educated about nutrition, in general, as well as potential use of micronutrient powder to improve the nutritional quality of complementary foods. Keywords: anemia, low birth weight, dietary intake, predictors, under-five children